2019
DOI: 10.1097/ta.0000000000002476
|View full text |Cite
|
Sign up to set email alerts
|

Delayed interhospital transfer of critically ill patients with surgical sepsis

Abstract: Background: Suboptimal triage of critically ill patients with surgical sepsis may contribute to adverse outcomes. Patients transferred to a tertiary care center after spending ≥24 hours at an outside facility were compared with patients who had early triage to a tertiary care center with the null hypothesis that management parameters and outcomes would be similar between groups.Methods: This prospective observational cohort study included 308 patients treated for surgical sepsis in a surgical intensive care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…The authors reported that delayed transfer patients had higher SOFA scores. 32 While not a traditional trauma scoring tool, SOFA was selected in EpiC by a 20-member expert panel 33 as a trade-off between high feasibility of collecting the necessary clinical variables despite slightly lower performance characteristics compared with other trauma multiorgan failure scoring tools. 21,34 The correlation of critical interventions with organ failure scores and trends, especially as they pertain to prolonged periods of resuscitation and delays to care, will be an ongoing area of focus in the EpiC study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that delayed transfer patients had higher SOFA scores. 32 While not a traditional trauma scoring tool, SOFA was selected in EpiC by a 20-member expert panel 33 as a trade-off between high feasibility of collecting the necessary clinical variables despite slightly lower performance characteristics compared with other trauma multiorgan failure scoring tools. 21,34 The correlation of critical interventions with organ failure scores and trends, especially as they pertain to prolonged periods of resuscitation and delays to care, will be an ongoing area of focus in the EpiC study.…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients with a wide range of complex disease processes often require expeditious transfer to tertiary or quaternary institutions' emergency departments (EDs) and intensive care units (ICUs) for a higher level of care. Decreasing time to definitive care at high-volume centers can improve outcomes in various patient populations, and it is for this reason that in July 2013, the critical care resuscitation unit (CCRU) was established at the University of Maryland Medical Center (UMMC)'s R Adams Cowley Shock Trauma Center (STC) [ 1 5 ]. The CCRU was designed to be a multispecialty resuscitation unit that receives both medical and surgical patients, typically from Maryland, Delaware, and Virginia.…”
Section: Introductionmentioning
confidence: 99%
“…Установлено, что чем выше степень дисфункции жизненно важных систем пациента, тем в большей мере он подвержен рискам при транспортировке и, соответственно, тем более негативным может быть результат лечения [4][5][6][7]. В доступной литературе мы не встретили сравнительных исследований по выживаемости пациентов, которые, находясь в критическом состоянии, подвергались медицинской эвакуации и в процессе транспортировки получали вазопрессорную поддержку.…”
Section: Introductionunclassified